Baking and cooling of biscuits. what happens in a baking oven, types of oven, post-oven processing, cooling, handling, troubleshooting tips - Manley, Duncan (Biscuit, cookie and cracker manufacturing manuals, 1998)
This manual explains the principles and machinery involved in baking and post-baking processes, and the key issues in maintaining both quality and throughput.